Misleading advertising of the food industry as a strategy to incentivize consumption even in the face of the enactment of the junk food law - Noguera Cardona, Joan Sebastián; Sánchez Castillo, Verenice (Southern perspective / Perspectiva austral, 2024)
Objective: to know the characteristics of misleading advertising in the food industry as a strategy to encourage consumption even with the enactment of the junk food law - 2021. Method: qualitative, descriptive research is carried out with a family from the municipality from Pitalito in the department of Huila, the instrument used was the interview. Results: the calorie intake of ultra-processed foods is an indicator of nutritional quality, these foods have a lower nutritional quality than fresh or minimally processed foods combined. Discussions: nutrition messages that appear on food labels deserve special attention, due to misinformation and misleading advertising. Junk Food Project 167 of 2019 is aimed at improving this information. Conclusions: It is necessary for the food industry to guarantee the full protection and prevalence of consumer rights. Various sectors of society and the government itself have mobilized in favor of the drafting of more restrictive legislation in relation to the advertising of unhealthy foods and beverages directed at children